Characterization, Molecular Identification and Antimicrobial Susceptibility Testing of Diarrheagenic Escherichia coli Isolated from Diarrhea Infected Patients Around Dhaka City - Fahima Akter; Md. Shamimuzzaman; Susmita Roy Chowdhury; Faria Islam; Rajib Kanti Roy (RADS Journal of Biological Research & Applied Science)
Background: Mostly Escherichia coli is an innocuous intestinal inhabitant and does not cause infection or disease in a healthy individual. Nevertheless, Shiga toxigenic Escherichia coli (STEC) is one of the few strains that causes severe diarrheal disease in humans all over the world, where tropical and developing countries have a higher incident rate.